1967
DOI: 10.1113/jphysiol.1967.sp008290
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary vasoconstriction and changes in heart rate during asphyxia in immature foetal lambs

Abstract: SUMMARY1. The effect of changing the composition of pulmonary arterial blood on the pulmonary vasoconstrictor response to asphyxia was studied in immature foetal lambs of 90 days gestation age.2. When normal foetal carotid arterial blood (withdrawn before asphyxia) was introduced during asphyxia, the pulmonary vasoconstriction was rapidly and wholly relieved as soon as this blood reached the lung. This did not happen when blood was used which had been withdrawn during asphyxia.3. Conversely introduction into a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

1967
1967
1989
1989

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 18 publications
2
26
0
Order By: Relevance
“…It was not practicable to attempt bilateral thoracic sympathectomy after completion of the preparation. However, it had been observed that stimulation of the post-ganglionic sympathetic fibres arising from the third to fifth ganglia on the left side, as they run across the posterior thoracic wall to reach the left hemiazygos vein, causes left pulmonary vasoconstriction in both mature (Colebatch, Dawes, Goodwin & Nadeau, 1965) and immature foetal lambs (Campbell et at. 1967).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It was not practicable to attempt bilateral thoracic sympathectomy after completion of the preparation. However, it had been observed that stimulation of the post-ganglionic sympathetic fibres arising from the third to fifth ganglia on the left side, as they run across the posterior thoracic wall to reach the left hemiazygos vein, causes left pulmonary vasoconstriction in both mature (Colebatch, Dawes, Goodwin & Nadeau, 1965) and immature foetal lambs (Campbell et at. 1967).…”
Section: Resultsmentioning
confidence: 99%
“…In the preceding paper (Campbell, Dawes, Fishman & Hyman, 1967) it was concluded that, in immature foetal lambs, the effect of asphyxia in causing pulmonary vasoconstriction was mainly, if not exclusively, due to a local action within the lungs. The following experiments were designed to determine whether asphyxia would still cause pulmonary vasoconstric -112 A.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations